Activity of spinal RORβ neurons is related to functional improvements following combination treatment after complete SCI - Nicholas J. Stachowski; Jaimena H. Wheel; Shayna Singh; Sebastian J. Atoche; Lihua Yao; D. Leonardo Garcia-Ramirez; Simon F. Giszter; Kimberly J. Dougherty (Proceedings of the National Academy of Sciences, 2025)
Various strategies targeting spinal locomotor circuitry have been associated with functional improvements after spinal cord injury (SCI). However, the neuronal populations mediating beneficial effects remain largely unknown. Using a combination therapy in a mouse model of complete SCI, we show that virally delivered brain-derived neurotrophic factor (BDNF) (AAV-BDNF) activates hindlimb stepping and causes hyperreflexia, whereas submotor threshold epidural stimulation (ES) reduces BDNF-induced hyperreflexia. Given their role in gating proprioceptive afferents and as a potential convergence point of BDNF and ES, we hypothesized that an enhanced excitability of inhibitory RORβ neurons would be associated with locomotor improvements. Ex vivo spinal slice recordings from mice with a range of locomotor and hyperreflexia scores revealed that the excitability of RORβ neurons was related to functional outcome post-SCI. Mice with poor locomotor function after SCI had less excitable RORβ neurons, but the excitability of RORβ neurons was similar between the uninjured and “best stepping” SCI groups. Further, chemogenetic activation of RORβ neurons reduced BDNF-induced hyperreflexia and improved stepping, similar to ES. Our findings identify inhibitory RORβ neurons as a target population to limit hyperreflexia and enhance locomotor function after SCI.